Travail et santé chez les prostituées : entre imaginaire et réalité - Vanessa Andrade de Barros (Perspectives Interdisciplinaires sur le Travail et la Santé)
The ideas presented in this article are the result of an action-research undertaken over a four-year period between 2006 and 2009 with prostitutes from the poor districts of Belo Horizonte (Brazil). The psychosociology of work in combination with ergology are the key theoretical and methodological references in this article. Considering prostitution as work, we first present the various dimensions of this activity within the Brazilian context before exploring the relationship between health and work for these professionals and the strategies these women employ to take care of their health.